Mikhail Lomonosov and Vuk Karadžić : a study of two language reformers - Mueller, Felicity (The Australian National University, 1978)
The various modern Slavonic literary languages developed between the second half of the eighteenth century and the first half of the twentieth century . Russian and Polish are the only Slavonic languages which were able to develop without experiencing any interruption of their literary traditions, i.e. they are the only Slavonic languages which have a continuous literary tradition.